(untitled) - Valsson, Bragi Þór

Heyr, himna smiður: the sacred a cappella SATB works of Þorkell Sigurbjörnsson (1938-2013) (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)-- Stellenbosch University, 2022.